The Autoimmune Protocol Diet Modifies Intestinal RNA Expression in Inflammatory Bowel Disease. Issue 3 (12th July 2019) - Chandrasekaran, Anita; Molparia, Bhuvan; Akhtar, Ehsaan; Wang, Xiaoyun; Lewis, James D; Chang, John T; Oliveira, Glenn; Torkamani, Ali; Konijeti, Gauree Gupta
Lay Summary: Researchers from the Scripps Clinic in La Jolla, CA recently looked at gene expression to better understand the role that diet plays in inflammatory bowel disease. Their findings suggest that diet may help modify inflammatory pathways in people with ulcerative colitis.